THE EFFECTIVENESS OF POLICY FOR UNDERGRADUATE STUDENTS NOT REQUIRING THESIS AS A GRADUATION REQUIREMENTON STUDENT QUALITY - Eri Mardiani; Linda Handayani; Antonius Rino Vanchapo; Nunung Suryana Jamin; Murthada (CV. ADIBA AISHA AMIRA, 2023)
The Ministry of Education, Culture, Research and Technology changed the obligations of undergraduate students in completing their final assignment not only with a thesis but expanded into several options which include projects, prototypes, and so on which were fully handed over to universities. Therefore, this research aims to analyze the effectiveness of this policy using the SWOT analysis technique. This research is qualitative research with a descriptive approach. The research results show that this policy has a number of weaknesses and threats in the future. Researchers assess that this policy will not be effectively implemented in the Indonesian education system.